The bank capital channel and bank profits. Issue 3 (14th February 2019) - Orzechowski, Paul E.
Abstract: This paper develops a microeconomic model of banking to highlight an endogenous loan creation process that emerges from bank profits via the capital accumulation of retained earnings and uses a simple bank capital‐loan multiplier to illustrate constraints on lending. The study also analyzes how sufficient net interest margins are important for banks to maintain lending portfolios and avoid financial fragility. The model offers support to bank capital channel (BKC) economists by illustrating how changes in interest rates may influence bank lending through the bank's internal capital accumulation growth rate and on a bank's portfolio choices.